Establishing midwife-led continuity of care interventions in perinatal mental health in high-risk pregnancies: a best practice implementation project. (17th September 2022) - Morlans-Lanau, Miriam; González-Vives, Maria L.; Rodríguez-Quiroga, Alberto; Casbas, Mayte M.; Klugarová, Jitka; Klugar, Miloslav
ABSTRACT: Objectives: The current best practice implementation project aimed to improve the quality of continuity of care and emotional well-being in women with high-risk pregnancies. Introduction: Perinatal mental health disorders, such as perinatal depression and anxiety, are considered major health issues and are associated with poor maternal and neonatal outcomes. Women with high-risk pregnancies are considered a group of women with a substantial vulnerability and the value of continuity of care is vital in this group. Methods: The current project used the pre–post implementation clinical audit following the JBI Evidence Implementation framework. A baseline audit and a follow-up audit were conducted involving 120 high-risk pregnant women in a hospital's obstetric unit. An intervention was performed establishing a midwife consultation and a referral circuit for the different healthcare professionals. A screening was performed through several validated questionnaires. Results: To reflect the continuum of care, three topics were selected, including antenatal psychosocial assessment, intrapartum care and postpartum depression assessment, with a total of 10 criteria. The baseline audit results showed 0% compliance in all the criteria since the proposed standards of care did not exist before the audit. After the implementation of the strategies, the compliance achieved 100% in all audit criteria. A multidisciplinary hospital guideline was established for standardized care and mental well-being care for high-risk pregnant women. Conclusion: Follow-up in the mental health of pregnant women is insufficient. Improving emotional well-being in pregnancy should be a target of clinical practice. More national and international guidelines to assess mental well-being during pregnancy and the postpartum period should be developed.